Análise dos aspectos motores e ambientais na qualidade de vida da população idosa da área urbana e rural de um município do semiárido brasileiro - Sousa, Marcos Saulo Patrício de (Universidade Federal Rural do Semi-Árido, 2018)
The quality of life has been well evidenced due to the human activities developed in the last decades, causing problems like pollution and significantly altering the atmospheric conditions of the planet. Among the factors that cause pollution, bioaerosols deserve attention. Knowledge of the microbiological quality of air becomes necessary, since the control and minimization of these variables bring a series of benefits, among which a better quality of sleep, greater aerobic resistance and consequently a better quality of life for the elderly. Through this perspective, the objective of the present study is to analyze the motor and environmental aspects in the elderly regarding the quality of life of the urban and rural zone in the city of Mossoró-RN, Brazil. The study was carried out at the Reference Center for Social Assistance, CRAS - Bom Jardim, and in the Cordão de Sombra I and II settlements, between March and August 2017. 60 elderly individuals were selected, 28 males and 32 females, 30 from each locality, between 60 and 72 years. For the analysis of the quality of life, the WHOQOL-BREF (World Health Organization Quality of Life) questionnaire was used in the physical and environmental domains. The subjects were submitted to a physical evaluation, to a battery of tests of the Protocol GDLAM (Latin American Development Group for Maturity) to the questionnaire on afforestation. And still the quantification of bacteria and fungi was carried out in their dormitories. The results showed that there was only a correlation between the quality of life and the age, considered strong and inversely proportional in both locations, no significant statistical differences between the localities were observed. Regarding the motor variables analyzed, the urban area presented a better quality of life among the evaluated elderly. Among the environmental variables, the rural area was classified as having a better quality of life, with better afforestation rates, but with a higher quantification of bacteria and fungi. Among the environmental variables there was no significant correlation between the quality of life and the analyzed variables. A significant difference was verified through the 1% F test, in the quantification of bacteria and fungi between the localities. The rural zone obtained greater quantification of bacteria and fungi, where the genus Bacillus sp. was the most frequent, and the fungus was Aspergillus niger. It was concluded that the quality of life in relation to the physical aspects was better in the urban zone, whereas among the environmental aspects it was better in the rural area
Keywords: Idosos; Aspectos motores; Aspectos ambientais; Micro-organismos; Elderly; Motor aspects; Environmental aspects; Micro-organisms; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE